As transferências fiscais no federalismo brasileiro: sobre o repasse do FUNDEB ao Estado do Maranhão - BRANDÃO, Gustavo Furtado (2019)
The objective of this research is to analyze the impacts of FUNDEB on the financing process of basic education in the State of Maranhão, verifying the capacity and effectiveness of this Fund in achieving its strategic objectives to promote the decentralization of this level of education and establish a national policy of decrease inequalities. In order to evaluate the fiscal impacts of FUNDEB, this research will cover the historical context of Brazilian federalism and the model of fiscal federalism adopted by the Federal Constitution of 1988. Through FUNDEB, the states are benefited by financial resources from the Union. the central assumption of this research. In this way we seek to analyze the trajectory of financial resources available to the State of Maranhão. With this, it is tried to verify if the FUNDEB represents a fundamental category for the federative balance in the financing of the education, especially of the fundamental education. In this research, the relationship between social policy and federalism in Brazil is sought in light of the state model created by the 1988 Constitution and the limits imposed by fiscal federalism.